PENGARUH MOTIVASI KERJA, KEPEMIMPINAN, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT XYZ - DIMAS ASTAGINA; ARIEF ALFIANDRY (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to determine whether there is an influence between work motivation, leadership, and organizational culture on employee performance at PT. XYZ. The sample in this study was 65 employees. The sampling technique is based on purposive sampling. This study used a questionnaire to collect data. The data analysis method used is multiple linear regression. The results of this study reveal that there is an influence between work motivation, and organizational culture with employee performance, but there is no influence between leadership and employee performance.